PENYULUHAN DAMPAK GAME ONLINE PADA KESEHATAN ANAK, PENCEGAHAN PENYAKIT DEGENERATIF, SKRINING KESEHATAN, PEMERIKSAAN FORMALIN DAN EDUKASI DAGUSIBU OBAT DI PULAU PANGGANG KEPULAUAN SERIBU JAKARTA - Mutawalli Sjahid Latief; Bayu Eriyanto; Adelia Unayah; Dian Rahmat Haryanto; Lala Makbulah; Rizky Damayanti; Lilistiatun (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Background: counseling is an effort to provide knowledge, invite people to be aware so that they can form proper attitudes and behavior in life, counseling about online games, prevention of degenerative diseases. Health checks, formalin checks and education about Dagusibu are concerns for maintaining public health. Objective: to increase public understanding, especially parents regarding online games, degenerative diseases and the drug Dagusibu, to identify the presence of formaldehyde content in food and public health screening. Method: Community service activities were carried out on Panggang Island, Seribu Islands, DKI Jakarta Province. Results: the community service activities that have been carried out have resulted in all activities running smoothly, starting from counseling, distributing questionnaires and leaflets regarding the impact of online games on children's psychological health, counseling and distributing questionnaires regarding the prevention of degenerative diseases, health screening (checking blood sugar levels, Cholesterol and uric acid levels), distribution of multivitamins, checking for formaldehyde preservatives in food, searching for marine biota samples and education and distribution of leaflets regarding Dagusibu (Get, Use, Save, Throw Away) Medicine. Keyword; Counseling. Screening, Education.